Kenya : 2004 Article IV Consultation, First Review Under the Poverty Reduction and Growth Facility, and Requests for Augmentation of Access, Rephasing of the Arrangement, and Waiver of Performance Criteria; Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report ;, 2009)
This 2004 Article IV Consultation highlights that monetary policy of Kenya has been expansionary since 2003/04 to promote economic growth. This has, however, contributed to the recent rise in inflation. Executive Directors have observed the progress that has been made under the Poverty Reduction and Growth Facility (PRGF)-supported program, which has contributed to a rebound in economic growth and arrested the rise in domestic debt. However, Directors have noted that Kenya faces serious challenges. In particular, growth remains too slow for making inroads into poverty, and governance remains a critical concern.